Alaqah Al-Kafa'ah As-Syakhsyiyah Li Al-Mu'allimin Ala Ihtimam Ta'allum Al-Lugah Al-Arabiyah Lada Tullab Al-Madrasah Ats-Tsanawiyah Al-Ahliyah Ira Medan - Nurfasilah, Nurfasilah; Zulheddi, Zulheddi (Al-Lahjah : Jurnal Pendidikan, Bahasa Arab, dan Kajian Linguistik Arab, 2025)
This study aims to examine the relationship between the personality of Arabic language teachers and students’ interest in learning Arabic. The research employs a quantitative method with a correlational approach. The population consists of all students at MTs Ira Medan, with a sample of 28 students selected through random sampling. Data were collected using a closed-ended questionnaire that had been tested for validity and reliability. Data analysis was conducted using the Pearson Product Moment correlation formula. The results indicate a statistically significant relationship between teacher personality and students’ learning interest, with a significance value of 0.00 (p < 0.05) and a correlation coefficient of 0.669, which falls into the strong category (0.61–0.80). This value exceeds the r table (0.374), leading to the conclusion that there is a strong positive relationship between teacher personality (X) and students’ interest in learning (Y), with a contribution of 44.7%. These findings highlight the importance of teacher personality development as a key factor in enhancing students' interest in learning Arabic.